Management of Catheter-Related Urethral Injuries in Male Children - Muhammad Shahid Bhatti, Muhammad Daraz Khan, Sajid Abbasi, Reena Nawaz, Mohammad Sajjad, Hassan Raza Asghar, Farman Ullah (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Urethral injuries in male children, particularly those related to catheter insertion, are rare but serious complications that require prompt diagnosis and appropriate management. These injuries can result in significant long-term morbidity, affecting the urinary system and quality of life. This study aims to evaluate the management strategies for catheter-related urethral injuries in male children and assess their outcomes. Objective: To assess the management approaches and outcomes of catheter-related urethral injuries in male pediatric patients. Methodology: This retrospective study conducted at Department of Urology and transplantation Pir Abdul Qadir Shah Institute of Medical sciences Gambat from February 2022 to February 2023. It included 95 male pediatric patients diagnosed with catheter-related urethral injuries. Data were collected from medical records, including demographic information, injury details, treatment methods (conservative vs. surgical), and post-treatment outcomes, such as recovery time, complications, and long-term function. Results: Out of the 95 patients, 65% were treated conservatively, while 35% required surgical intervention. The mean recovery time for conservative cases was 4.0 weeks, and for surgical cases, it was 6.0 weeks. Complications occurred in 12% of the cases, with 8% requiring additional interventions. The majority of patients (90%) had a good long-term functional outcome with no significant urinary issues at follow-up. Conclusion: Both conservative and surgical treatments were effective for managing catheter-related urethral injuries in male children. Conservative management was successful in the majority of cases, while surgical intervention was necessary for more severe injuries. Prompt diagnosis and appropriate management are critical to minimizing long-term complications. Keywords: Urethral injuries, catheter-related injuries, pediatric urology, conservative management, surgical intervention, urinary complications.